Learning to read in multilingual Malaysia: a focus on bahasa Melayu, Tamil and Chinese - Winskel, Heather (Penerbit Universiti Kebangsaan Malaysia, 2020)
Learning to read fluently is an extremely important skill for all children to acquire. The current article focuses on learning to read in the most widely spoken languages of Malaysia, namely, the national language Bahasa Melayu, Tamil and Chinese. These three unrelated languages have quite distinct writing systems. Bahasa Melayu uses alphabetic Rumi or Roman script, Tamil has an alphasyllabary, and Chinese has a logographic or morphosyllabic writing system. Moreover, many of these children are learning to speak and read in more than one language. When we consider the task of these biscriptal learners, a complex picture emerges, as they may have to learn to map different phonological and orthographic systems. Furthermore, many children in Malaysia have the additional challenge of learning English as a second language. First, a brief review of the characteristics of the three main languages and their orthographies is given. Subsequently, research on phonological awareness, an important skill associated with success in reading, is reviewed. Initially, phonological awareness and reading in single language studies is examined prior to reviewing some research on bilingual learners. As these three languages have rich morphological systems, we will also briefly examine some research on morphological awareness and reading. A review of the literature reveals that children who speak a language with a similar orthography to a second language may have some advantage when learning to read that second language in comparison to children whose first and second languages and orthographies are unrelated.